2012
DOI: 10.1186/1756-3305-5-242
|View full text |Cite
|
Sign up to set email alerts
|

Defining parasite biodiversity at high latitudes of North America: new host and geographic records for Onchocerca cervipedis (Nematoda: Onchocercidae) in moose and caribou

Abstract: BackgroundOnchocerca cervipedis is a filarioid nematode of cervids reported from Central America to boreal regions of North America. It is found primarily in subcutaneous tissues of the legs, and is more commonly known as ‘legworm’. Blackflies are intermediate hosts and transmit larvae to ungulates when they blood-feed. In this article we report the first records of O. cervipedis from high latitudes of North America and its occurrence in previously unrecognized host subspecies including the Yukon-Alaska moose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…There is a need to reassess the type-material of O. cervipedis , and to further characterize specimens collected from the two hosts, and ideally from the original localities using integrated classical and molecular tools. At this stage, it cannot be determined if either O. cervipedis sensu Verocai et al, 2012 [ 11 ] or the cryptic species isolated in the present study and in the skin of WTD in New York belong to O. cervipedis as originally described. The potential for zoonotic infections among species of Onchocerca establishes the need to characterize the recently recognized cryptic species, to explore for broader currently hidden diversity and to define the host and geographical limits within this assemblage.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…There is a need to reassess the type-material of O. cervipedis , and to further characterize specimens collected from the two hosts, and ideally from the original localities using integrated classical and molecular tools. At this stage, it cannot be determined if either O. cervipedis sensu Verocai et al, 2012 [ 11 ] or the cryptic species isolated in the present study and in the skin of WTD in New York belong to O. cervipedis as originally described. The potential for zoonotic infections among species of Onchocerca establishes the need to characterize the recently recognized cryptic species, to explore for broader currently hidden diversity and to define the host and geographical limits within this assemblage.…”
Section: Discussionmentioning
confidence: 70%
“…To date in North America only one species, O. cervipedis , has been formally described and has been reported to infect five species of cervids and the pronghorn [ 8 , 11 , 12 ]. Our work provides further evidence for the existence of a cryptic, undescribed species of Onchocerca associated with wild ungulates in North America [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…flies are known to be vectors for several Onchocerca species for which sequence data are not available ( 33 , 34 ). However, previous studies have suggested that sequence variation in the mitochondrial genome varies from 7% to 15% among Onchocerca species ( 9 , 35 ), and intraspecies variation within the mitochondrial genome is limited in the genus Onchocerca ( 9 , 35 ). Therefore, the sequences detected in the flies are unlikely to have derived from a species other than O. lupi .…”
Section: Discussionmentioning
confidence: 98%